Resin-based sealants longevity: a clinical evaluation - Araujo, Heitor Ceolin; Faria, Isabela Copetti; Torquato, Brenda Zanfolin; Araujo, Renan Ceolin; Prado, Rosana Leal do; Takahashi, Karine (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Introdution: The occlusal surface of the molars are more susceptible to dental caries because of their anatomy, so in some cases, the sealants are indicated. Objective: The objective of this study was to evaluate the efficacy, retention, presence of caries and marginal discoloration of resinous sealants (Fluoroshield and Prevent) in first permanent molars. Methods: Ninety - one children aged 7 to 9 years were selected from a municipal institution Regente Feijó, SP, Brazil, for the application of resinous sealants to first permanent lower first molars. The application of Fluoroshield and Prevent resin sealants was performed according to the manufacturer's recommendations. The evaluation was performed after 6 and 12 months by double-blind examiners and followed the criteria: alpha (total sealant, absence of caries and absence of pigmentation) charlie (partial sealing, superficial caries and light pigmentation) charlie complete sealing, presence of cavitation and pigmentation) after 12 months of application by two previously calibrated examiners. Results: Using Fischer's exact test, no significant difference (p> 0.05) was observed between the resin-based sealant groups. In the evaluated criteria, both sealants after three years were similar, and may therefore be suitable materials for sealing grooves and fissures in permanent molars. Descriptors: Pit and Fissure Sealants; Dental Caries; Dentition, Permanent; Oral Health. References Palma-Dibb RG, Chinelatti MA, Souza-Zaroni WC. Diagnóstico de lesões de cárie. In: Assed S. Odontopediatria: bases científicas para a prática clínica. São Paulo: Artes Médicas; 2005. Sheiham A, James WP. Diet and Dental Caries: The Pivotal Role of Free Sugars Reemphasized. J Dent Res. 2015;94(10):1341-47. Faleiros Chioca S, Urzúa Araya L, Rodríguez Martínez G, Cabello Ibacache R. Uso de sellantes de fosas y fisuras para La prevención de caries em población infanto-juvenil: Revisión metodológica de ensayos clínicos. Rev Clin Periodoncia Implantol Rehabil Oral. 2013;6(1):14-9. Liu BY, Lo EC, Chu CH, Lin HC. Randomized Trial on Fluorides and Sealants for Fissure Caries Prevention. J Dent Res 2012;91(8):753-58 Condò R, Cioffi A, Riccio A, Totino M, Condò SG, Cerroni L. Sealants in dentistry: a systematic review of the literature. Oral Implantol (Rome). 2014;6(3):67-74. Ahovuo-Saloranta A, Forss H, Walsh T, Hiiri A, Nordblad A, Mäkelä M et al. Sealants for preventing dental decay in the permanent teeth. Cochrane Database Syst Rev. 2013;(3):CD001830 Moreira KMS,Kantovitz KR,Aguiar JPD, Borges AFS, Pascon FM, Puppin-Rontani RM. Impact of the intermediary layer on sealant retention: a randomized 24-month clinical trial. Clin Oral Investig. 2017;21(5):1435-43. Griffin SO, Gray SK, Malvitz DM, Gooch BF. Caries Risk in Formerly Sealed Teeth. J Am Dent Assoc 2009;140(4):415-23. Splieth CH, Ekstrand KR, Alkilzy M, Clarkson J, Meyer-Lueckel H, Martignon S et al. Sealants in dentistry: outcomes of the ORCA Saturday Afternoon Symposium 2007. Caries Res. 2010;44(1):3-13 Sundfeld RH, Briso ALF, Mauro SJ, de Alexandre RS, Sundfeld Neto D, Oliveira FG et al. Twenty years experience with pit and fissure sealants. Int J Clin Dent. 2010;2(4):1-12. Baldini V, Tagliaferro EPS, Ambrosano GMB, Meneghim MC, Pereira AC. Use of occlusal sealant in a community program and caries incidence in high- and low-risk children. J Appl Oral Sci. 2010;19(4):396-402. Provenzano MGA, Rios D, Fracasso MLC, Marchesi A, Honório HM. Clinical Evaluation of a Resin-Modifi ed Glass Ionomer Cement (Vitremer®) Used as Pit-And-Fissure Sealant in Primary Molars. Pesq Bras Odontoped Clin Integr.2010;10(2):233-40. Saito CM, Lima EP, Mello D, Mello FAS. Selante resinoso: tratamento preventivo e minimamente invasivo. Rev Gest Saúde. 2014;11:10-17. Zenkner JE, Alves LS, de Oliveira RS, Bica RH, Wagner MB, Maltz M. Influence of eruption stage and biofilm accumulation on occlusal caries in permanent molars: a generalized estimating equations logistic approach. Caries Res. 2013;47(3):177-82. Delmondes FS, Imparato JCP. Selamento de primeiros molares permanentes em erupção com cimento de ionômero de vidro. J Bras Odontopediatr. Odontol Bebê. 2003;6(33):373-78. Heyduck C, Meller C, Schwahn C, Spliet CH. Effectiveness of Sealants in Adolescents with High and Low Caries Experience. Caries Res. 2006;40(5):375-81. Tagliaferro EPS, Ambrosano GMB, Meneghim MC, Pereira AC. Risk indicators and risk predictors of dental caries in schoolchildren. J Appl Oral Sci. 2008;16(6):408-13. Silva RCSP, Araujo MAM, Rego MA. Avaliação clinica de selantes de fossulas e fissuras: efeitos de materiais e tempo de analise. Rev Odontol UNESP. 1996;25(2):237-45. Beraldo DZ, Pereira KFS, Zafalon EJ, Yoshinari FMS.Análise comparativa entre selante resinoso e selante ionomérico por microscópio eletrônico de varredura. Rev Odontol UNESP. 2015;44(4):239-43. Araújo IT, Cunha MMF, Vasconcelos MG, Vasconcelos, RG. Selantes: uma técnica eficaz na prevenção da cárie. Com ciênc saúde. 2013;24(3):259-66. Moura SK, Lemos LVFM, Myszkovisk S, Provenzano MGA, Balducci I, Myaki SI. Bonding durability of dental sealants to deciduous and permanent teeth. Braz J Oral Sci. 2014; 13(3):198-202. Sundfeld RH, Mauro SJ, Briso ALF, Sundfeld MLMM. Clinical/photographic evaluation of a single application of two sealants after eleven years. Bull Tokyo Dent Coll. 2004;45(2):67-75. Folke BD, Walton JL, Feigal RJ. Occlusal Sealant Success Over Ten Years in a Private Practice: Comparing Longevity of Sealants Placed by Dentists, Hygienists, and Assistants. Pediatr Dent. 2004;26(5):426-32. Sundfeld RH, Croll Theodore P, José MS, Briso ALF, Sversut AR, Sundefeld MLMM. Longitudinal photographic observation of the occurrence of bubbles in pit and fissure sealants. J Appl Oral Sci. 2006;14(1):27-32. Arhakis A, Damianaki S, Toumba KJ. Pit and fissure sealants: types, effectiveness, retention, and fluoride release: a literature review. Balkan J Stomatol. 2007;11(3):151-62. Garbin CAS, Garbin AJI, Santos KT, Pizzato E, Moroso TT. Retention of a pit-and-fissure sealant: comparison of three types of isolation. Pesq Bras Odontoped Clin Integr. 2008;8(2):175-78. Kühnisch J, Mansmannb U, Roswitha HW, Hickel R. Longevity of materials for pit and fissure sealing - results from a meta-analysis. Dent Mater. 2012;28(3):298-303.